2021
DOI: 10.5539/elt.v14n2p9
|View full text |Cite
|
Sign up to set email alerts
|

A Correlational Study of the English Listening and Speaking Anxiety in Rural Areas

Abstract: English proficiency amongst Malaysian is debatably on a decline. Possible causes of this phenomenon are extensively argued. Thus, renewed interest towards English language anxiety, an internal factor of learners’ level of intensity in listening and speaking skills, can sometimes be overlooked. An investigation was conducted on selected secondary schools' students in Selangor, a state in Malaysia. The schools lacked facilities and meagerly equipped with basic resources and facilities. A total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 14 publications
(25 reference statements)
1
7
0
Order By: Relevance
“…Note that a decline in anxiety for one skill, such as listening, can reduce anxiety for other related skills, such as speaking when the two anxiety skills are correlated. If there is a link, then reducing or eliminating anxiety in the listening skill may result in a reduction in anxiety in the speaking skill as a result of the input skill's anxiety reduction (Hamid & Idrus, 2021).…”
Section: Challenges Faced By Esl Learners In Malaysia To Speak English Languagementioning
confidence: 99%
“…Note that a decline in anxiety for one skill, such as listening, can reduce anxiety for other related skills, such as speaking when the two anxiety skills are correlated. If there is a link, then reducing or eliminating anxiety in the listening skill may result in a reduction in anxiety in the speaking skill as a result of the input skill's anxiety reduction (Hamid & Idrus, 2021).…”
Section: Challenges Faced By Esl Learners In Malaysia To Speak English Languagementioning
confidence: 99%
“…Since AR can provide additional digital content for any difficult-to-understand subject, a substantial amount of literature on its use in educational contexts has been published [3,4]. For example, Xue et al, [5] demonstrated that the most frequently cited positive effect of using AR in education is user satisfaction.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The traditional chalk-and-talk teaching method and the use of static textbooks are failing to engage students, leading to poor learning outcomes and shorter periods of attention in a traditional class environment, and their interests can be easily distracted [24]. Hence, students become bored and easily fall asleep during class due to their inability to visualise certain concepts provided in the textbooks [4]. The introduction of technology-based approaches such as AR provides a supportive environment for all children's learning.…”
Section: Augmented Reality Application For Children In Malaysiamentioning
confidence: 99%
“…A total of 15 studies adopted situation-specific-based scales to measure FL listening anxiety, with 10 studies (15.2%) measuring general listening anxiety and five studies (7.6%) measuring listening test anxiety. Other studies that employed various approaches to measure FL listening anxiety were only minimally present; for example, seven studies measured FL listening anxiety under the approach of the sources of anxiety; eight studies measured FL listening under the approaches of learner characteristics and FL listening ability, Kim, 2000Kim, , 2011Kimura, 2008;Bekleyen, 2009;Wang, 2010Wang, , 2016Kiliç and Uçkun, 2012;Mohammadi Golchi, 2012;Capan and Karaca, 2013;Pae, 2013;Serraj and Noordin, 2013;Tsai, 2013;Afshar and Hamzavi, 2014;Choi and Chon, 2014;Movahed, 2014;Yamauchi, 2014b;Li, 2015;Rahimi and Soleymani, 2015;Zhai, 2015;Bang and Hiver, 2016;Berber and Gönen, 2017;Cheng, 2017;Halat and Özbay, 2018;Jee, 2018;Namaziandost et al, 2018;Babakhouya and Elkhadiri, 2019;Kutuk et al, 2019;Ranto Rozak et al, 2019;Fathi et al, 2020;Hutapea et al, 2020;Hamid and Idrus, 2021;Niimoto, 2021 Emotionality 33 50.0 Tension over English, emotionality, affective, listening anxiety Kim, 2000Kim, , 2011Kimura, 2008;Bekleyen, 2009;…”
Section: Measuring Foreign Language Listening Anxietymentioning
confidence: 99%